2017
DOI: 10.5171/2017.800299
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Security Behaviour among Higher Education Students in Malaysia

Abstract: This study explores the current state of cyber security behaviour among higher education students in Malaysia. The respondents' cyber security behaviour was assessed in the following aspects: password usage, phishing, social engineering, online scam and malware. A questionnaire comprised of the aforementioned five cyber security issues was distributed to students in a well-established university college located in the Northern region of Peninsular Malaysia. The returned questionnaires were analyzed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 1 publication
3
45
0
1
Order By: Relevance
“…More malware attacks may mean that there is a need to increase the CSA in universities. The study also concurs with previous studies that suggested that there is a need for CSA in universities to minimize malware attacks on students 40‐42 …”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…More malware attacks may mean that there is a need to increase the CSA in universities. The study also concurs with previous studies that suggested that there is a need for CSA in universities to minimize malware attacks on students 40‐42 …”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The study also concurs with previous studies that suggested that there is a need for CSA in universities to minimize malware attacks on students. [40][41][42] The IoT attack is positively related to CSA was supported in this study. More devices are being connected to the internet and there is a need for CSA in university students so that the IoT attack may be reduced.…”
Section: Discussion Of Findingssupporting
confidence: 67%
“…Providing knowledge to upgrade teachers' and students' understanding of cyber issues is one step that could be taken by relevant parties to protect such groups from evolving cybersecurity threats [31]. Cybersecurity awareness education is important to protect internet users from potential cybercrimes as well as evolving cyber threats.…”
Section: B Strategies That Stakeholders Can Use To Promote Cybersecumentioning
confidence: 99%
“…Based on the study conducted on the cybersecurity behavior, students at higher learning has shown high possibilities of being vulnerable to cyber security threats which could possibly eliminated with sense of awareness of the threats. Cybersecurity knowledge and awareness education would become shield, defending the students from the evolving cybercrimes and cyberthreats (Muniandy L, Muniandy B & Samsudin, 2017). According to Latif and Abdul-Rahman (2018), lack or absence of knowledge in money laundering is seen from the aspect of understanding of financial crime, legal and related laws, and the importance of fight against money laundering and socio-economy impact when someone participates in this crime.…”
Section: Awareness As Prevention Toolmentioning
confidence: 99%